Ethno-social tourist values of Branicevo District - Trišić, Igor (Hotel and Tourism Management, 2017)
Branicevo district is rich with different types of tourist values. It is characterized by diverse landforms such as mountain areas as Homolje and Zvižd; plains along the rivers of Danube, Morava, Mlava and Stig. This region is inhabited by a population whose cultural values can make the significant share of tourist offer in this part of country. Ethno-social values of Vlachs, together with local community and tourist organizations support, can create interesting tourist entertainment programs, adjusted to all age groups and interests.